Emergency remote instruction in 2020: Differential impacts on science, technology, engineering, and mathematics students’ confidence and belonging, by gender, race/ethnicity, and socioeconomic status - Brown, Nathanial; Zipf, Sarah; Pagoto, Sherry; Waring, Molly E.; Hatfield, Neil; Palmer, Lindsay; Lewis, Katherine A.; Workman, Deja (Frontiers in Education, 2022)
The COVID-19 pandemic forced higher education into emergency remote instruction in 2020. Impacts of this modality shift on undergraduates of different identities are important to document, for both current students who need support now and future students who may face other crises. A large survey in the United States asked students in science, technology, engineering, and mathematics (STEM) to report the impact of emergency remote instruction on their confidence to succeed and sense of belonging in STEM. Using those data, we find that the impact varies by gender, race/ethnicity, and socioeconomic status (SES). For instance, 63.3% of lower SES women identifying as underrepresented racial/ethnic minorities (URM) reported a decrease in their confidence to succeed, compared to 38.9% of non-URM, higher SES men who reported a decrease. On the other hand, 35.3% of URM, lower SES men reported that emergency remote instruction increased their sense of belonging, compared to 15.9% of non-URM, higher SES women. The large percentage reporting increased belonging was unexpected and adds to calls for more research into the experiences of URM men. Our results suggest researchers, instructors, and administrators working to mitigate shocks to higher education must consider multiple identities and take an intersectional view, because impacts of these crises are not neutral with respect to gender, race/ethnicity, and SES.